Nanoparticle surface coatings produce distinct antibacterial effects that are consistent across diverse bacterial species - Ameh, Thelma; Zarzosa, Kuzy; Braswell, W. Evan; Sayes, Christie M. (Frontiers in Toxicology, 2023)
Nanoparticles have been proposed as tunable delivery vehicles for targeted treatments and, in some cases, the active therapeutic agents themselves. Despite the promise of such customizable impacts, little evidence exists to support these claims in the realm of antibiotics. Exploration of the silver and copper nanoparticle antibacterial impacts have been reported with inconsistent results. Here, we investigate the physical, chemical, and bacterial properties of silver and copper core particles stabilized with commonly used surface coatings, namely, polyvinylpyrrolidone (PVP, to confer a neutrally charged surface), cetrimonium bromide (CTAB, positively charged surface), citrate (Cit, negatively charged surface for silver nanoparticles), and ascorbic acid (AA, negatively charged surface for copper nanoparticles. The impacts of these potential antibacterial nanoparticles are measured against three bacterial species spanning deep divisions in the bacterial tree of life and include Escherichia coli, Staphylococcus aureus, and Sphingobacterium multivorum. Varying dose, core composition, surface coating, and bacterial species revealed that nanoparticle surfaces accounted for most of the variation in antibacterial activity. In all experiments, dose produced a linear inhibitory effect. Surprisingly, bacterial species reacted similarly regardless of evolutionary relatedness. There is a high degree of consistency, effectiveness, and efficacy among PVP silver and copper nanoparticle. These findings have implications for the intentional use of nanotechnology in environmental systems.